Decoding: codes and hardware implementation - Sulzer, M.P. (1983)
MST radar vary considerably from one installation to the next in the type of hardware, operating schedule, associated personnel, and amount of funding. Most such systems do not have the computing power to decode in software when the decoding must be performed for each received pulse, as is required for certain sets of phase codes. These sets allow one to obtain the best signal-to-sidelobe ratio when operating at the minimum baud length allowed by the bandwidth of the transmitter. We discuss here a number of realizations of the hardware phase decoder, and discuss the applicability of each to decoding MST radar signals. We present a new design for a decoder which is very inexpensive to build, easy to add to an existing system and is capable of decoding on each received pulse using codes with a baud length as short as one microsecond.